2008
DOI: 10.1021/op700222r
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Practical Route for the Manufacture of N-[5-(3-Imidazol-1-yl-4-methanesulfonyl-phenyl)-4-methyl-thiazol-2-yl]acetamide

Abstract: An efficient synthesis of a potent candidate in our respiratory program is described. The synthesis based on a key Darzens condensation-r,β-epoxide rearrangement circumvented the toxicity and safety issues encountered in the original synthesis route. Subsequent functionalization and formation of an heterocyclic moiety is presented with a particular emphasis on the practicality, robustness, and streamlining of the process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Given the poor efficiency of this oxidation process (in total, 10 equiv of the oxidant KHSO 5 were required, when only 2 are theoretically needed) the use of alternative oxidants has been briefly examined. Both sodium tungstate/hydrogen peroxide and peracetic acid have given promising preliminary results and will be the focus of further development.…”
Section: Introductionmentioning
confidence: 99%
“…Given the poor efficiency of this oxidation process (in total, 10 equiv of the oxidant KHSO 5 were required, when only 2 are theoretically needed) the use of alternative oxidants has been briefly examined. Both sodium tungstate/hydrogen peroxide and peracetic acid have given promising preliminary results and will be the focus of further development.…”
Section: Introductionmentioning
confidence: 99%
“…As an alterative to m -CPBA, aqueous hydrogen peroxide has been shown in the literature to be one of cheap and green oxidants . Sulfone synthesis via a molybdate- or tungstate-catalyzed sulfide oxidation with aqueous hydrogen peroxide has been well-documented. We then quickly evaluated the efficiency of Na 2 WO 4 -catalyzed oxidation of sulfide 6 with 30% aqueous H 2 O 2 in a variety of solvents (Table ). It was found that EtOH (entry 1) gave an incomplete conversion after 7 h. Reactants were not completely soluble in this solvent system, resulting in a heterogeneous reaction.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…2 Since the seminal work of Erlenmeyer and Darzens, the methodology has been extensively used for aromatic aldehydes as well as for aromatic and aliphatic ketones. 3 During the reaction, a carbonyl is reacted with an a-halo ester in the presence of a base to give an epoxide.…”
mentioning
confidence: 99%